Imido-transfer reactions to carbonyl moiety induced by the reactions of imido-bridged cobaltadithiolene complexes with trivalent phosphorus halides - Nomura, Mitsushiro (Animo Repository, 2003)
The reactions of the imido-bridged cobaltadithiolene complexes [CpCo{S 2 C 2 (COOMe) 2 }(NR)] (R=Ts, Ms) with PCl 3 led to the imido-transfer reactions to the carbonyl moiety, and these reactions gave the novel imine complexes [CpCo{S 2 C 2 (COOMe)(C=NROMe)}]. In the case of PI 3 , another imido-transfer reaction to carbonyl moiety occurred and the novel amide complexes [CpCo{S 2 C 2 (COOMe)(CONHR)}] were formed. PBr 3 showed an intermediate reactivity value in between that of PCl 3 and that of PI 3 . Both novel imido-transfer reactions were caused by intermolecular reactions, these reaction processes were determined by crossover experiments. © 2003 Elsevier Science B.V. All rights reserved.